2020
DOI: 10.3390/su12177072
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mixed Hardwood Biochar, Mycorrhizae, and Fertigation on Container Tomato and Pepper Plant Growth

Abstract: Biochar (BC) has the potential as a peat moss alternative for container plant growth. Three experiments were conducted to evaluate the effects of mixed hardwood BC, compost types, mycorrhizae, and fertigation on container-grown tomato and pepper growth. In experiment 1 (Exp1), BC at 50%, 70%, and 90% (vol.) were mixed with 5% vermicompost (VC) with the rest being a commercial peat moss-based substrate (CS) and fertigated at 200 or 300 mg L−1 N. In experiment 2 (Exp2), 80% BC was mixed with chicken manure compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The addition of biochar to peat-based media increases porosity in substrates, as well as cation exchange capacity (CEC), pH, and potassium [18,19]. The average price of biochar is almost half as the price of peat moss [20]. Biochar helps to lower the economic cost used to produce horticultural crops in nursery industries by replacing the peat moss up to certain levels [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of biochar to peat-based media increases porosity in substrates, as well as cation exchange capacity (CEC), pH, and potassium [18,19]. The average price of biochar is almost half as the price of peat moss [20]. Biochar helps to lower the economic cost used to produce horticultural crops in nursery industries by replacing the peat moss up to certain levels [20].…”
Section: Introductionmentioning
confidence: 99%
“…The average price of biochar is almost half as the price of peat moss [20]. Biochar helps to lower the economic cost used to produce horticultural crops in nursery industries by replacing the peat moss up to certain levels [20]. The production cost of biochar can also be lowered if it can be produced onsite with local resources and avoid long distance transportation [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement in the nitrogen use efficiency (NUE) of crops can not only reduce planting costs, but also reduce energy consumption related to chemical fertilizer production, which fundamentally alleviates global climate change [ 58 , 59 ]. Combined application of biochar and chemical nitrogen fertilizer (e.g., urea) can effectively raise crop yield and NUE by slowing down nitrogen release, regulating microbial diversity, and stimulating nitrification while inhibiting denitrification, as compared with applying chemical fertilizer as the sole nitrogen source [ 60 62 ]. There are many studies focused on the increased nitrogen agronomic efficiency resulted from the improved soil nitrogen availability with biochar application, but there are few reports on molecular signals or root phenotypes related to nitrogen availability increase in rhizosphere [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biochar has been used as a soil amendment due to its positive effects on altering the biological and physicochemical properties of soils 8 , it also has the potential use as a substrate in container nurseries to improve substrate water and nutrient holding capacity, ameliorate acidity, and provide suitable environments for plant growth 9,10 . Studies had shown that biochar could partially replace peat moss-based substrate for greenhouse ornamental and vegetable plants production 11,12 or used as an additional amendment in substrate to improve crop growth, yield, and quality [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%